Highly improved pH-Responsive anticancer drug delivery and T2-Weighted MRI imaging by magnetic MOF CuBTC-based nano/microcomposite - Gharehdaghi, Zahra; Naghib, Seyed Morteza; Rahimi, Rahmatollah; Bakhshi, Atin; Kefayat, Amirhosein; shamaeizadeh, Armin; Molaabasi, Fatemeh (Frontiers in Molecular Biosciences, 2023)
In this paper, we have developed a magnetic nanoscale MOF by introducing Fe3O4 nanoparticles into the porous isoreticular MOF [Cu3(BTC)2] for drug delivery purposes. The developed magnetic nanoscale MOF was characterized using various techniques including XRD, IR, BET, FESEM, and VSM to study the impact of nanoparticles on the metal organic framework structure. Some properties of the resulting magnetic MOFs are large surface area, high magnetic response, large mesopore volume, high transverse relaxivity (r2) and pH responsive behavior. According to the results a high loading capacity (40.5%) of DOX on magnetic MOFs was obtained. The release profile of DOX showed that at a pH of 5, the released amount of DOX was 83%, while the DOX release was below 30.5% for a pH of 7.4 within the same 48 hours period. The MOF biocompatibility was observed using cytotoxicity tests with HeLa and 3T3 cells. The magnetic MOFs had negligible cytotoxicity, meanwhile DOX-loaded magnetic MOFs had a significant cellular uptake which improved HeLa cell-killing ability. Moreover, the magnetic MOFs had a higher T2-weighted magnetic resonance imaging contrast, which increased the image significance. Moreover, Annexin V staining method was used to evaluate the cytotoxicity of loaded and free DOX. These studies suggest that the magnetic MOFs may be used for clinical purposes and especially delivering anticancer drugs.